THE EFFECT OF SPORT MASSAGE ON LACTIC ACID RECOVERY - Mohamad Brilian; Surdiniaty Ugelta; Pipit Pitriani (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study was to determine the extend of the impact of the sports massage recovery method on the lactate levels of wrestling athletes. The population in this study was West Java PON wrestling athletes with purposive sampling technique with the criteria of having participated in national level championships and male gender with a total of 4 person. The instrument in this study was the Wrestling Match Simulation, Sport Massage is a recovery method protocol with a duration of 20 minutes, Acutend Lactate to measure the athlete's lactate level before and after being given the treatment. The results showed that there was a significant decrease in the athlete's lactate level after being given the treatment.